Industry Restructuring, Mark-ups, and Exchange Rate Pass-Through - Beverly Lapham; Danny Leung (Queen's University, Department of Economics, 2006)
Consumer prices are not very responsive to movements in nominal exchange rates and their response has fallen in Canada since the mid 1980s. This paper explores two of the most likely explanations for this decline in exchange rate pass-through to consumer prices: (1) lower inflation and (2) restructuring in the retail sector. We believe that both explanations are important but our primary focus in this paper is on the second explanation. We discuss the restructuring that has occurred in Canadian retail and trends in mark-ups and concentration in that sector. We argue that to understand these trends, it is important to examine pass-through in industrial organization models with strategic elements. Finally, we present a series of such models and evaluate the effects of various forms of restructuring on mark-ups, concentration, and exchange rate pass-through.
Keywords: D40; F15; F31; F41; L16; 330; Pass-Through; Restructuring; Strategic Pricing; Mark-ups; Exchange Rates; Imperfect Competition; Exchange Rate Pass-Through; Verbraucherpreisindex; Inflationsrate; Einzelhandel; Organisatorischer Wandel; Kanada